Pengaruh Kampanye Ingat Pesan Ibu terhadap Sikap Patuh Protokol Kesehatan pada Masyarakat Kabupaten Karawang - Zalfa Salsabila Aulia Putri; Christin, Maylanny (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
In the midst of the Covid-19 pandemic that is currently spreading, the government is intensifying actions so that the Indonesian people are obedient in implementing the Covid-19 prevention health protocol. One such action is to intensify the "Remember Mom's Message" campaign. This campaign is intensified in various regions in Indonesia including the Karawang Regency area. This study aims to analyze the influence of the Remember Mother's Message campaign on protocol compliance attitudes in the people of Karawang Regency. This research uses quantitative research with survey methods. Sampling was carried out using the probability sampling method with a simple random sampling type with the people of Karawang Regency as the population. This study used descriptive and inferential data analysis techniques. Based on the t-test that has been carried out, it shows that the H0 which states the Remember Mother's Message Campaign has a significant effect on the Karawang Regency Public Health Protocol Compliance Attitude is rejected and H1 which states that the Remember Mother's Message Campaign has a significant effect on the Karawang Regency Public Health Protocol Compliance Attitude is accepted. The amount of influence of the Remember Mother's Message Campaign on protocol compliance attitudes in the Karawang Regency community obtained from the determination coefficient test was 67.4%. This shows that the Remember Mother's Message Campaign has an influence of 67.4% on Ptotokol's Obedient Attitude, while the remaining 32.6% is influenced by other factors or variables that are not studied. Keywords: Attitude, Communication, Campaign, Effect, Protocol